1994
DOI: 10.1159/000126763
|View full text |Cite
|
Sign up to set email alerts
|

Prolactin Gene Expression in Ovine and Caprine Mammary Gland

Abstract: The presence of prolactin (PRL) mRNA in the mammary gland of lactating goats and sheep was demonstrated by Northern analysis and RT-PCR. This provides evidence that the PRL gene is transcribed in this tissue. This ectopic expression is not restricted to the lactational period, as PRL transcripts were also found during the last third of pregnancy. Comparison of mammary and pituitary PRL mRNAs showed that they are similar in size but less abundant in mammary gland. In addition, an 847-bp cDNA fragment amplified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0
5

Year Published

1997
1997
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(35 citation statements)
references
References 39 publications
3
27
0
5
Order By: Relevance
“…Subsequently, no relationship between the level of circulating PRL and the amount of PRL mRNA could be established. This variability was also reported in other species [12,13].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Subsequently, no relationship between the level of circulating PRL and the amount of PRL mRNA could be established. This variability was also reported in other species [12,13].…”
Section: Discussionsupporting
confidence: 86%
“…The PRL mRNA has been observed in several cell types [6][7][8][9], including mammary epithelial cells (MEC) of lactating rat, goat, sheep and rabbit [10][11][12][13] and of normal and neoplastic tissue [14]. Newly synthesized PRL has been detected in a breast cancer cell line [15].…”
Section: Introductionmentioning
confidence: 99%
“…Decidual/lymphoid type PRL transcripts were detected in some, but not all mammary tissues and cells (Shaw-Bruha et al, 1997), while a study performed in goat and sheep showed that the size of the mammary gland mRNA is similar to the pituitary hPRL mRNA (Le Provost et al, 1994).…”
Section: Introductionmentioning
confidence: 91%
“…Prolactin gene disruption experiments proved its important roles in mammary gland development (mammogenesis), lactogenesis, maintenance of milk secretion (galactopoiesis), and expression of milk protein genes [10]. It is also chiely accountable for synthesis of lactose, lipids, and all other major components of milk [11]. Consequently, the bovine prolactin gene seems to be an outstanding candidate for linkage analysis with quantitative trait loci (QTL) afecting milk production traits.…”
Section: Prolactinmentioning
confidence: 99%